In Vivo Quantification of Myocardial Infarction in Mice Using Micro-CT and a Novel Blood Pool Agent. (16th October 2017) - Sawall, Stefan; Franke, Danielle; Kirchherr, Anne; Beckendorf, Jan; Kuntz, Jan; Maier, Joscha; Kraupner, Alexander; Backs, Johannes; Briel, Andreas; Kachelrieß, Marc
Abstract : We herein developed a micro-CT method using the innovative contrast agent ExiTron™ MyoC 8000 to longitudinally monitor cardiac processes in vivo in small animals. Experiments were performed on healthy mice and mice with myocardial infarction inflicted by ligation of the left anterior descending artery. Time-dependent signal enhancement in different tissues of healthy mice was measured and various contrast agent doses were investigated so as to determine the minimum required dose for imaging of the myocardium. Due to its ability to be taken up by healthy myocardium but not by infarct tissue, ExiTron MyoC 8000 enables detection of myocardial infarction even at a very low dose. The signal enhancement in the myocardium of infarcted mice after contrast agent injection was exploited for quantification of infarct size. The values of infarct size obtained from the imaging method were compared with those obtained from histology and showed a significant correlation (R 2 = 0.98 ). Thus, the developed micro-CT method allows for monitoring of a variety of processes such as cardiac remodeling in longitudinal studies.